Estudo comparado entre bibliotecários, contadores e analistas de tecnologia da informação: processo de profissionalização e seu efeito na formação, atuação e reconhecimento profissional - Josmaria Lima Ribeiro de Oliveira (2012)
Throughout the 90s and in the beginning of the current century, neolibera States and the movements for productive redructuration have had impacts on professions that were thus driven into processes of deregulation, in favor of flexibility of professional formation and labor relations. The fields related to information and communication were notably striken. Such movements affect the deregulation of labor market and professions, generating an impact not only on characteristics of qualification, jurisdiction and control but also on changing professional peformance, wage relation and profesional education. Besides, thereis an impact on regulatory and control actions of the respective professionaI certification. With the weakening of regulatory actions, there was a change in the way society acknowledges a profession, thus presenting a new profexiona perspective. Due to these changes, professions go through a moment of readaptation. In this perspective, the present work analyses questions about the value of professionaIization, taking into account the notions of wage and educational relation, by means of a comparative research among librarians, accountants and information technology analysts. Both quantitative and qualitative approaches were used as research methodology. Regarding qualitative data, 17 interviews were carried out with many social actors who represent the collective interest of employers, employees, schools and society. The quantitative data included the data base RAIS (Brazilian Annual Report of Social Information) and RAISMIGRA (Migration Component of the Annual Report of Social Information) from 1985 to 2009, as well as the database PNAD (Brazilian National Research for Sample of Domiciles) from 2002, 2004, 2006 and 2008. The result validates the mimption that regulation contributes to professionaization. Concerning formation, one identified that the professions that had been |onger regulated have more articulation with social actors, since they solve problems within the professional community, thus causing minor constraints to society. Regarding professional performance, it was possible to identify that professions that had been longer regulated present more favorable conditions to prevent structura unemployment, maintain skilled work force, the possibility of mobility and stability, wage and social acknowledgment